1980
DOI: 10.1139/f80-117
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Scales in Phytoplankton Ecology. Mechanisms, Methods, Models, and Management

Abstract: Depcarfrnurzf of Biology, Mcil4usfer fiiversify, Hamilfort, Onr. HARRIS, G. P. 1980. Temporal and spatial scales in phytoplankton eco1ogy. Mechanisms, methods, models, and management. Can. 3. Fish. Aquat. Sci. 319: 879-900.This article is essentially a review of the temporal and spatial scales iaf variability in both marine and freshwater planktonic environnlents and the algal responses to those scales. I assert that therc are problerns with our present understanding of thew scales and the use of imapprapriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
2
14

Year Published

1984
1984
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(152 citation statements)
references
References 41 publications
(54 reference statements)
6
130
2
14
Order By: Relevance
“…The presence of such long-scale temporal shifts indicate that the small time scales of the immediate growth environment cannot sufficiently account for the success of a species. Harris (1980) has stressed that more attention should be paid to the various time scales of phytoplankton response to its environment. He suggested that smaller time scales would be of greater importance.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such long-scale temporal shifts indicate that the small time scales of the immediate growth environment cannot sufficiently account for the success of a species. Harris (1980) has stressed that more attention should be paid to the various time scales of phytoplankton response to its environment. He suggested that smaller time scales would be of greater importance.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers that practice landscape ecology recognise that ecological patterns and processes operate at a range of scales in time and space and that many organisms respond to this hierarchically. This organism-based perspective means that 'habitat' and the relevant patterns and processes in the surrounding environment are defined and scaled by the activities and responses of the organisms of interest (Wiens, 1976;Harris, 1980;Addicott et al, 1987;Morris, 1987;Wiens and Milne, 1989;Kotliar and Wiens, 1990;Pearson et al, 1996;McAlpine et al, 1999).…”
Section: Spatial Hierarchymentioning
confidence: 99%
“…The response of the microbial community to these event scale phenomena will depend upon the frequency and duration of the pulse (Harris, 1980;Robarts et al, 1998). For example, short-term events have physiological consequences whereas long-duration events could lead to species shifts and ecosystem change.…”
Section: Evidence For and Consequences Of A Pulsed Nutrient Supplymentioning
confidence: 99%